TEACHING SPEAKING NARRATIVE MONOLOGUE BY USING SHRINKING STORY STRATEGY - Firmansyah, .; ., Sudarsono; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purpose of this research is to find out the level of effectiveness of the use shrinking story strategy in teaching speaking narrative monologue to twelfth grade students of SMA Negeri 1 Semparuk in academic year 2013/2014. This research was a pre-experimental research with one group pre-test and post-test design. The population of this research were twelfth science grade students. The samples of this research were twelfth science one students. The technique of data collecting was measurement technique. The data were collected by applying pre-test and post-test through speaking narrative monologue performance orally and were analyzed by using speaking scoring criteria. The final computation shows that the effect size of the treatment is 1.55 (>0.8) and considered strong effect. It proves that the use of shrinking story strategy is highly-effective to teach speaking narrative monologue to twelfth science students. Key Words: Teaching, Narrative Monologue, Shrinking Story. Abstrak: penelitian ini bertujuan untuk menetahui tingkat keefektifan pengunaan strategy shrinking story dalam mengajarkan berbicara naratif dalam bentuk monolog kepada siswa kelas dua belas tahun ajaran 2013/2014. Penelitian ini adalah sebuah penelitian eksperimental dengan rancanggan satu grup pre-test dan post-test. Populasi dalam penelitian ini adalah siswa-siswa kelas dua belas ilmu alam. Sample penelitian ini adalah siswa kelas duabelas ilmu alam satu. Teknik pengumpulan data adalah teknik pengukuran. Data-data diambil dengan menerapkan pre-test dan post-test melalui penampilan berbicara naratif monolog secara lisan dan kemudian dianalisa menggunakan criteria penilaian berbicara. Perhitungan akhir menunjukkan bahwa effect size dari perlakuan adalah 1.55 (>0.8) dan dikatakan tinggi. Hal tersebut membuktikan bahwa penerapan strategy shrinking story sangat efektif untuk mengajar berbicara naratif monolog pada siswa kelas duabelas ilmu alam. Kata kunci: pengajaran, monolog naratif, shrinking story.